(untitled) (Psychology Travelogs, 2024)
The article notes that social and psychological trainings play a significant role in teaching communicative competence. It is indicated that training technologies are a synthesis of all active learning tools and contribute to the development of communicative competence in future psychologists. It is noted that communicative competence is a significant component in the professional competence of a psychologist. The structure of psychological competence of a psychologist is presented. The complex of personal characteristics of the social orientation of a psychologist and the complex of social competence, communicative competence, perceptual competence, psychological competence and autopsychological competence are described. The development of communicative competence in cadets-future psychologists is shown. It is noted that in a higher educational institution in the specialty «Psychology» cadets are offered «Training of professional abilities development» and «Psychotraining» in order to form their communicative competence. It is indicated that «Training for the Development of Professional Abilities» and «Psychotraining» are aimed at developing professional knowledge, communication skills of future psychologists, reflective skills, the ability to analyze the situation, behavior, condition of clients and their personal condition; the ability to respond quickly to the situation and change according to the situation in different conditions of activity; the ability to adequately perceive oneself and others. The article presents techniques for developing active, attentive and purposeful listening; reflective listening (echo technique, paraphrasing, summarizing); formulating and asking questions; ability to establish and give and receive feedback; empathic attitude towards the client.